A comparison of the effect of application of sodium ascorbate and amla (Indian gooseberry) extract on the bond strength of brackets bonded to bleached human enamel: An In vitro study - Shivani Keni; Supriya Nambiar; Pramod Philip; Siddarth Shetty (Wolters Kluwer Medknow Publications, 2018)
Introduction: Whitening of teeth is a popular choice among dental clinicians and patients. However, the changes in enamel structure and composition induced by the bleaching agents cause a decrease in the shear bond strength of brackets leading to premature bracket debonding. Among several methods to overcome this, the most common is delaying bonding by 2-4 weeks. This waiting period can be eliminated by applying an antioxidant (sodium ascorbate) which causes a reversal in the reduction of bond strength. Aim: This study aims to compare the efficacy of a naturally occurring antioxidant (gooseberry) and sodium ascorbate in normalizing the bond strength of enamel to prebleached levels. Materials and Methods: Seventy-two extracted premolars were divided into 4 equal groups; 1st group - control group - unbleached teeth, bonded directly, 2nd group - bleached with 16% carbamide peroxide (8 h for 1 week), then bonded. 3rd and 4th group - similarly bleached, followed by application of 10% sodium ascorbate and gooseberry extract (3 h respectively), then bonded. Bond strength was checked using Instron Universal Testing Machine. Results: The bond strength of the control group was the highest and that of the carbamide group was drastically reduced. Considerable increase in the bond strength was seen after treatment with sodium ascorbate with negligible difference between sodium ascorbate and control group (P > 0.05). Conclusion: Treatment with gooseberry extract did improve the bond strength but was not as effective as sodium ascorbate postbleaching.